Persepsi Guru Terhadap Pengelolaan Kelas Yang Menyenangkan untuk Pembelajaran Anak Usia Dini - Salsabila, Shilfa Sukma; Utami , Winda Sherly (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine teachers' perceptions of fun classroom management in early childhood learning at Al-Moestafa Kindergarten, Jambi City. Effective and fun classroom management plays an important role in supporting aspects of child development. This study uses a qualitative approach with a descriptive method. Data collection techniques were carried out through questionnaires distributed in the form of online questionnaires (Google Form). The results of the study showed that teachers had positive perceptions of fun classroom management. Children looked comfortable in following the learning process, the classroom atmosphere was relatively conducive, and social interactions between children went well. Learning media have been utilized optimally, and children's ability to work together in groups shows good results. In general, teachers have played an active role in creating a fun learning environment that is in accordance with the developmental needs of early childhood.